2012
DOI: 10.1111/j.1471-8847.2012.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Integrity in Greater China: Surveying Regulations, Perceptions and Knowledge of Research Integrity from a Hong Kong Perspective

Abstract: In their 2010 article 'Research Integrity in China: Problems and Prospects', Zeng and Resnik challenge others to engage in empirical research on research integrity in China. Here we respond to that call in three ways: first, we provide updates to their analysis of regulations and allegations of scientific misconduct; second, we report on two surveys conducted in Hong Kong that provide empirical backing to describe ways in which problems and prospects that Zeng and Resnik identify are being explored; and third,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…Macfarlane and Saitoh (2008, p. 185), for example, noted that in Japan, research ethics was a "relatively new concept" for many of their 13 interviewees, all of whom were academic staff members. Jordan and Gray (2013) found that only half the academics that they approached in disciplines that conducted human research at the University of Hong Kong were even "somewhat familiar" with key research ethics principles (p. 132). In China and Indonesia, the two countries most represented by students in our own study, there are likely to be no human research ethics committee procedures for social research undertaken by university students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Macfarlane and Saitoh (2008, p. 185), for example, noted that in Japan, research ethics was a "relatively new concept" for many of their 13 interviewees, all of whom were academic staff members. Jordan and Gray (2013) found that only half the academics that they approached in disciplines that conducted human research at the University of Hong Kong were even "somewhat familiar" with key research ethics principles (p. 132). In China and Indonesia, the two countries most represented by students in our own study, there are likely to be no human research ethics committee procedures for social research undertaken by university students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…universities, research institutions, or national agencies like the ORI, handle allegations of scientific misconduct and investigate cases, thereby effecting retractions and influencing the visibility of scientific misconduct. A number of publications, more or less based on anecdotal evidence, refer to country-specific organizational processes for dealing with misconduct: the USA ( Price, 2013 ; Steneck, 1994 , 1999 ); Japan ( Normile, 2007 ; Slingsby et al, 2006 ); Canada ( Lytton, 1996 ); Brazil ( Lins and Carvalho, 2014 ); South Africa ( Rossouw et al, 2014 ); China ( Jordan and Gray, 2013 ; Ren, 2012 ; Zeng and Resnik, 2010 ); Nigeria ( Adeleye and Adebamowo, 2012 ); Spain ( Puigdomènech, 2014 ); the UK ( Chantler and Chantler, 1998 ; Khajuria and Agha, 2014 ); Korea ( Kim and Park, 2013 ); Scandinavia ( Nylenna et al, 1999 ); Germany ( Deutsch, 2006 ; DFG, 2005 ; Schiffers, 2012 ; von Bargen, 2013 ).…”
Section: Handling Of Misconduct and Retractions In Organizationsmentioning
confidence: 99%
“…These limited comparative empirical studies have indicated that the northern (and western) European countries are more advanced in their guidelines and training on research integrity. Though the impact on attitudes and practices remain in doubt [56] , education and training of research integrity are believed to improve an individual’s knowledge of research integrity and misconduct [57 , 58] . Influences of guidelines also depend on training and education of research integrity.…”
Section: Discussionmentioning
confidence: 99%